Misterium Najświętszego Imienia Jezus w liturgii Kościoła rzymskiego - Pałęcki, Waldemar (Poznańskie Studia Teologiczne, 2021)
According to the bible tradition, the name of a person determine its personality and dignity. Since the 18th century there is known commemoration of the most sacred name of Jesus in the liturgy of Roman Church. The essence of this devotion contains the liturgical texts assigned for that day. Especially many texts of the pre-Vatican liturgy point out the great importance of that day. After the Second Vatican Council the commemoration was removed from the liturgical agenda, but anew established in 2002. Analysis of the texts contained in missal and breviary show theological contain of that feast day. The base are words about the humiliation and glorification of the Servant of Yahwe derived from the second chapter of the Letter of Saint Paul to Philippians (Phil. 2:6–11) and from the Acts of Apostles. In that book it is said that the name of Jesus is the only one by which we can be saved (Acts 4:8–12). Liturgical texts from the Old Testament indicate the fulfilment of the prophecy in the name of Jesus. Different motivation of praising the name of Jesus is shown in the literature of Christian writers who demonstrate the beauty and sweetness of the name of Jesus. Before The Second Vatican Council, in the sermons of St. Bernard it is highlighted that this name is innate, not given. Saint Bernard from Siena said in his sermons that the name of Jesus is the name of His mercy. This text is the base of the Office of readings after the Second Vatican Council. Nowadays this feast is celebrated on 3rd January and links the mystery of the nativity and of the revelation of the Lord, pointing out the unity in the celebration of the mystery of Incarnation.